2004
DOI: 10.1177/0363546503262166
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Reconstruction in High School Baseball Players

Abstract: The success rate of ulnar collateral ligament reconstruction in high school baseball players is nearly equal to that in more mature groups of throwers. Overuse of the throwing arm and throwing breaking pitches at an early age may be related to their injuries. Special attention should be paid to elite-level teenage pitchers who throw with high velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
359
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(368 citation statements)
references
References 9 publications
6
359
2
1
Order By: Relevance
“…7,17 The UCL is the primary stabilizer against valgus stress at the elbow, 8,13 and disruption of this ligament can lead to instability during the late cocking phase of the throwing motion. 7,12 It has been reported that the number of UCL reconstructions in high school baseball players has risen dramatically, due in part to the year-round opportunities for competition and training.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,17 The UCL is the primary stabilizer against valgus stress at the elbow, 8,13 and disruption of this ligament can lead to instability during the late cocking phase of the throwing motion. 7,12 It has been reported that the number of UCL reconstructions in high school baseball players has risen dramatically, due in part to the year-round opportunities for competition and training.…”
mentioning
confidence: 99%
“…7,12 It has been reported that the number of UCL reconstructions in high school baseball players has risen dramatically, due in part to the year-round opportunities for competition and training. 17 The etiology of UCL injury is likely multifactorial. Kibler and Sciascia 11 proposed that inadequate range of motion (ROM) and poor balance may significantly affect an athlete's ability to transfer energy along the kinetic chain, resulting in dysfunctional movement and increased stresses at various segments, including the elbow.…”
mentioning
confidence: 99%
“…The average age of all pitchers was 17 years (range [15][16][17][18]. The players pitched on average 2.2 seasons previously at the high school level.…”
Section: Methodsmentioning
confidence: 99%
“…This is easily demonstrated by observing the significant increase in the number of Major League Baseball pitchers who have undergone UCL reconstruction between the years 1986 and 2012 [11•]. Further proof of this upsurge is noted when considering the alarming increase in high school athletes undergoing this same surgery [12].…”
Section: Valgus Instabilitymentioning
confidence: 99%